LUMBUNG PADI DALAM KARYA SENI GRAFIS GAYA SUREALIS PADA MASYARAKAT KERINCI - Jeki Aprisela H; Andar Indra Sastra; Dharsono Dharsono (Jurusan Seni Rupa, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2018)
ABSTRACT The aim of the study was to realize the transformation of the granary aspect in the form of surrealist-style graphic art in the background of Kerinci community culture. Rice granaries for the Kerinci community not only as a place to store rice in the past, then also have a social dimension that gives kerinci community identity and relations. The qualitative method is used in this study by relying on observation, in-depth interviews to conduct analysis that can sharpen the imagination of the graphic arts media. The results of this study concluded that the rice barn is still a cultural icon of the Kerinci community. Rice barns also have a deep meaning, can be used as a foundation to look for values ​​as a living guide for the Kerinci community so that it can be used as an example, because the philosophy of the rice granary is to teach about togetherness and cohesiveness in society. In the past the community worked together to harvest rice and collect their crops to be collected, because they already knew that saving money or collecting results meant they formed cooperation in the community so that they could help other disadvantaged citizens.